"Empowering" Instead of "Crushing an Idea": One Student Teacher/Mentor Teacher Pair's Story of Learning and Growing. Issue 3 (2nd July 2020) - Wexler, Lindsay Joseph
ABSTRACT: This study shares the story of a mentor teacher and student teacher during a yearlong student teaching experience. It looks at how working with an educative mentor (prepared and supported to enact this role) can make a difference in the instructional practices and beliefs of a novice teacher, specifically by providing the student teacher with the opportunity to experiment and by the mentor being open to learning in his/her own teaching practice.